Anomaly in the orientation angle of morning side Pc5 geomagnetic pulsations observed at Syowa Station - Ken-ichi Kato (National Institute of Polar Research, 1996)
Pc5 geomagnetic pulsations observed in local morning at Syowa Station (SYOW) often show anomalous polarization characteristics in the horizontal plane. The sense of polarization of Pc5 pulsations observed at SYOW is the same as that at the other stations in the southern polar region. The orientation of the main polarization axis at SYOW points to geomagnetic north, that at other stations to the geomagnetic northeast. The purpose of this study is to explain the anomaly in the orientation of the polarization axis of morning side Pc5 pulsations at SYOW and four stations near SYOW, two of which are located tens of km away from SYOW and hundreds of km from the other two antarctic stations. The results are as follows : 1) The anomaly in the orientation of polarization axis of Pc5 pulsations is large at SYOW with no local time dependence. 2) The anomaly is related to the difference in the phase of the H and the D components. It is especially affected by the phase variations of the D component. 3) The phase of the H component of Pc5 pulsations at SYOW shows about 10°lead and that of the D component about 30°lag. It is inferred that the origin of the anomaly of the orientation of polarization axis of Pc5 pulsations at SYOW is caused by a local effect due to inhomogeneous electric currents induced underground around SYOW.